Renal resistance thresholds during hypothermic machine perfusion and transplantation outcomes – a retrospective cohort study. (25th March 2018) - Sandal, Shaifali; Paraskevas, Steven; Cantarovich, Marcelo; Baran, Dana; Chaudhury, Prosanto; Tchervenkov, Jean I.; Sapir‐Pichhadze, Ruth
Summary: Renal resistance (RR), of allografts undergoing hypothermic machine perfusion (HMP), is considered a measure of organ quality. We conducted a retrospective cohort study of adult deceased donor kidney transplant (KT) recipients whose grafts underwent HMP. Our aim was to evaluate whether RR is predictive of death‐censored graft failure (DCGF). Of 274 KT eligible for analysis, 59% were from expanded criteria donor. RR was modeled as a categorical variable, using a previously identified terminal threshold of 0.4, and 0.2 mmHg/ml/min (median in our cohort). Hazard ratios (HR) of DCGF were 3.23 [95% confidence interval (CI): 1.12–9.34, P = 0.03] and 2.67 [95% CI: 1.14–6.31, P = 0.02] in univariable models, and 2.67 [95% CI: 0.91–7.86, P = 0.07] and 2.42 [95% CI: 1.02–5.72, P = 0.04] in multivariable models, when RR threshold was 0.4 and 0.2, respectively. Increasing risk of DCGF was observed when RR over the course of HMP was modeled using mixed linear regression models: HR of 1.31 [95% CI: 1.07–1.59, P < 0.01] and 1.25 [95% CI: 1.00–1.55, P = 0.05], in univariable and multivariable models, respectively. This suggests that RR during HMP is a predictor of long‐term KT outcomes. Prospective studies are needed to assess the survival benefit of patients receiving KT with higher RR in comparison with staying wait‐listed.